PERJANJIAN JUAL BELI DUKU DENGAN SISTEM IJON ANTARA PEMBELI DENGAN MASYARAKAT KECAMATAN MARO SEBO KABUPATEN MUARO JAMBI - Abdul Hariss (Jurnal Ilmiah Universitas Batanghari Jambi, 2013)
In addition to fruit ahead duku ripe fruit buds to take a long time and the payment of the purchase fruit duku not all at once, then that relationship is duku purchase a warranty and have the force of law, the parties ie the buyer with duku tree owner (seller) entered into a purchase agreement duku known in the community Maro Sebo is an agreement with the debt bondage system.Duku purchase agreement with bonded labor system in society Maro Sebo sub is actually very risky, because in addition to the agreement are not generally made in the form of written, also takes a long time and the results are uncertain. With agreements made quite risky, so in practice it is not always the implementation of a purchase agreement with a system of bonded labor duku running as it should, no event of default is even one party or both parties do not fulfill the agreement that has been agreed.A default in the execution of a purchase agreement with a system of bonded labor duku very possible encountered any obstacles, such as: 1) The desired result of the fruit duku not as expected; 2) Not so buy Duku fruit because it has no more money, and 3) Fruit duku sold or transferred to another party.Keyword : Agreement, Ijon Systems, Duku